The vlogger diaries confessions of an internet sensation - Collins, Tim 1975- (Michael O'Mara Books Limited, 2016)
If you can't make friends, make followers! This is the hilarious story of a teenage girl's journey from geeky nobody to online superstar -- sort of. Fourteen-year-old Olivia Warren hasn't made one friend since she started her new school. She's tried, but it's tough having just come out of a year of homeschooling. She doesn't have any of the essential skills trying to choose her favourite coffee just gave her the shakes and rank breath, no-make-up selfies don't really count if you don't own make-up, and snapchatting with her cat Loki lacked the key element of teenage recklessness. Time for a different approach to making friends time for a vlog! Not sure that her own personality is suited for it, Olivia gets Emma, a popular girl from her school, to be the face of the vlog, reading scripts that Olivia's pre-prepared. Olivia does everything she can think of to please her fans and the vlog soon takes off. Subscribers hit the millions, freebies start piling up on the doormat and before she knows it there's a book deal in the pipeline But things get sticky when Olivia is asked to make public appearances. Can Emma carry it off without the scripts? Or will Olivia be discovered as a fraud? And will Loki ever forgive her for that 'feline good' makeover episode?